New Developments in Russian Regulation of Navigation on the Northern Sea Route - Jan Jakub Solski (Arctic Review on Law and Politics, 2013)
The regime of navigation on the Northern Sea Route (NSR) is still largely based on legislation adopted by the Soviet Union, and features certain deviations in the way Russia’s international legal rights and obligations are implemented. In recent years the Russian Federation has demonstrated interest in revising NSR legislation with the preparation of one single comprehensive Federal Act on the NSR, and also a Federal Act to introduce amendments to pre-existing legislation. The latter option has gained the support of legislators, as the newly promulgated Federal Law on the NSR, dated July 28th 2012, No. 132 FZ, established grounds for further specific regulatory acts to have effect on commercial navigation on the waters of the route. The primary purpose of this article is to discuss the processes leading up to this long-awaited decision, as well as the implications of the new legislation for navigation on the NSR. The creative legal ambiguity of the Russian domestic legislation has historically allowed for divergent arguments, voiced by Russian scholars, in respect to the assumed legal basis for the Russian extended authority to regulate navigation on the NSR and the limitations thereof. Alternative views have provided grounds for different legislative proposals and for heated discussions leading to the adoption of the most recent law. This article will trace the development of the legal thinking in Russia with respect to the allocation of jurisdiction on the NSR.